Unraveling the physicochemical properties of fibrous ingredients to improve the reproductive performance of pigs - Muro, Bruno Bracco Donatelli (2024)
Dietary fiber plays a fundamental role in improving the sustainability of swine production. Few studies have evaluated the benefits of dietary fiber on the reproductive performance of female pigs. Additionally, most studies have used ingredients that are not suitable for the Brazilian market. Therefore, this thesis had two main objectives. The first was to develop a fiber supplement that incorporates ingredients with diverse physicochemical properties, including ingredients produced by the Brazilian agriculture industry. The second objective was to add this supplement to the diets of female pigs to enhance the understanding of the impact of dietary fiber on reproductive performance during critical phases of the reproductive cycle. To reach this goal, four studies were conducted. The first study evaluated the physicochemical properties of 16 fibrous ingredients suitable for the Brazilian market and their respective short-chain fatty acid profiles produced through in vitro fermentation. Guar gum, beet pulp, citrus pulp, and wheat bran were the ingredients with the greatest potential to provide benefits related to soluble fibers. In contrast, lignocellulose and soybean hull emerged as the main ingredients that showed characteristics of insoluble dietary fibers. Based on the results of the first study, six ingredients (guar gum, soybean hull, wheat bran, lignocellulose, beet pulp, and citrus pulp) were selected for the second study. The second study evaluated the effects of combining different fibrous ingredients in varying proportions on in vitro fermentation profile and in vitro degradation and on the production of short-chain fatty acids. From the results of the first two studies, a fibrous supplement composed of 40% wheat bran, 20% citrus pulp, 20% lignocellulose, and 10% guar gum was produced. The third study assessed the effects of including the fiber supplement in the pre-mating diets of gilts. The gilts supplemented with the fiber supplement had larger ovarian follicles, higher serum concentrations of 17β-Estradiol, and a larger area occupied by granulosa cells on the 20th day of the estrous cycle. Additionally, the conceptuses of the supplemented females showed a greater volume of chorioallantoic vesicles. Finally, the fourth study evaluated the effects of including the fiber supplement in the transition diet (provided from the 90th day of gestation to the 5th day postpartum) of sows and gilts. The females supplemented with the fiber supplement had shorter farrowing durations and softer feces on the two days preceding farrowing and on the day of farrowing, indicating a lower incidence of constipation. The litters born to females supplemented with the fibrous supplement had a lower incidence of diarrhea in the first week postpartum. However, the performance of the piglets at weaning was not affected. Therefore, the results of these studies can assist nutritionists and researchers in developing diets and/or nutritional technologies that minimize the challenges associated with the hyperprolificacy of modern female pig genotypes.